ANALISIS YURIDIS PELEPASAN AREAL HAK GUNA USAHA PT.PERKEBUNAN NUSANTARA II (PTPN II) KEPADA PT.KAWASAN INDUSTRI MEDAN (PT.KIM) - Lamtiur Imelda P Nababan; Syafruddin Kalo; Bismar Nasution; Dedi Harianto (USU LAW JOURNAL, 2014)
ABSTRACT The legal status the Management Rights No. 1, 2, and 3 has been owned by PT KIM (Persero) because there is no revocation of the Management Rights Certificate by the National Land Board, and there is no Court’s verdict which states that the Management Rights No. 1, 2, and 3 are revoked or no legal enforcement. The renunciation of the Leasehold Land Area No. 10 has been in accordance with the Decree of the Minister of Finance No. 89/KMK.013/1991 on the Guidance for Transfer of Ownership of fixed assets of State Owned Enterprises. Besides that, the renunciation of the leasehold land area is not in the status of dispute because the Leasehold Certificate No. 10 has been issued 5 (five) years and 3 (three) months, but Tugimin and associates do not file a complaint in the written form to the holder of the certificate and to the Head of the Land Office or do not file a complaint to he Court about the possession of land and about the issuance of Leasehold Certificate No. 10 on June 19, 1994. Therefore, based on Article 32, paragraph 3 of the Government Regulation No. 24/1997 on Land Registration, Tugimin and associates cannot file any complaint, and the resolution of dispute on the crop land in the leasehold land area of PTPN II, which has been renounced to PT KIM was done through mediation. Keywords: Judicial Analysis on the Renunciation of Leasehold Land Area of PTPN II to PT KIM